Iron-based and BRD4-downregulated strategy for amplified ferroptosis based on pH-sensitive/NIR-II-boosted nano-matchbox - Lujing Geng; Tong Lu; Huaqing Jing; Yue Zhou; Xiaoyang Liang; Jiao Li; Nan Li (Elsevier, 2023)
Ferroptosis (FPT), a novel form of programmed cell death, is characterized by overwhelming iron/reactive oxygen species (ROS)-dependent accumulation of lipid peroxidation (LPO). However, the insufficiency of endogenous iron and ROS level limited the FPT therapeutic efficacy to a large extent. To overcome this obstacle, the bromodomain-containing protein 4 (BRD4)-inhibitor (+)-JQ1 (JQ1) and iron-supplement ferric ammonium citrate (FAC)-loaded gold nanorods (GNRs) are encapsulated into the zeolitic imidazolate framework-8 (ZIF-8) to form matchbox-like GNRs@JF/ZIF-8 for the amplified FPT therapy. The existence of matchbox (ZIF-8) is stable in physiologically neutral conditions but degradable in acidic environment, which could prevent the loaded agents from prematurely reacting. Moreover, GNRs as the drug-carriers induce the photothermal therapy (PTT) effect under the irradiation of near-infrared II (NIR-II) light owing to the absorption by localized surface plasmon resonance (LSPR), while the hyperthermia also boosts the JQ1 and FAC releasing in the tumor microenvironment (TME). On one hand, the FAC-induced Fenton/Fenton-like reactions in TME can simultaneously generate iron (Fe3+/Fe2+) and ROS to initiate the FPT treatment by LPO elevation. On the other hand, JQ1 as a small molecule inhibitor of BRD4 protein can amplify FPT through downregulating the expression of glutathione peroxidase 4 (GPX4), thus inhibiting the ROS elimination and leading to the LPO accumulation. Both in vitro and in vivo studies reveal that this pH-sensitive nano-matchbox achieves obvious suppression of tumor growth with good biosafety and biocompatibility. As a result, our study points out a PTT combined iron-based/BRD4-downregulated strategy for amplified ferrotherapy which also opens the door of future exploitation of ferrotherapy systems.